How Does Fiscal Decentralization Affect Health Outcomes? Evidence from China - Chen C; Zheng M; Zhu J (Dove Medical Press, 2023)
Chen Chen,1,2,* Meng Zheng,1,2,* Junli Zhu1,2,* 1School of Public Health, Capital Medical University, Beijing, People's Republic of China; 2Research Center for Capital Health Management and Policy, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Junli Zhu, School of Public Health, Capital Medical University & Research Center for Capital Health Management and Policy, No. 10, Xitoutiao, Youanmen Wai, Fengtai District, Beijing, 100069, People's Republic of China, Tel +86 18701515093, Fax +86 01083911578, Email smallying@126.comBackground: The impact of fiscal decentralization on health outcomes still has not reached a consensus, and studies conducted in the context of the new round of fiscal and taxation system reform are even less available. China's fiscal decentralization system has its own special characteristics, so it is necessary to analyze the impact of fiscal decentralization on health outcomes before and after the new round of fiscal and taxation system reform in China.Methods: Panel data from 2007 to 2019 were obtained through China's Health Statistics Yearbook and China's Statistical Yearbook. The effects of fiscal decentralization on health outcomes before and after the reform are explored separately by SYS-GMM, which introduce a dynamical model with a lag period of the explained variables. The Hansen test is used to determine excessive identification. The AR(2) is used to determine whether the residual term of the differential equation has a second-order serial correlation.Results: Fiscal decentralization consistently had a negative impact on health outcomes, yet government health expenditures did not mediate the impact of fiscal decentralization on health outcomes. Fiscal decentralization had a positive effect on per capita government health expenditure before the new reforms, yet had a negative effect on the percentage of government health expenditures, both before and after the new reform.Conclusion: China's fiscal decentralization has caused local governments to pay insufficient attention to the construction of people's livelihoods, and the problem of insufficient government investment in health has not been improved. The new round of fiscal and taxation system reform has not reversed this situation either. It is recommended to adjust the incentive system for local officials, include medical and health in the evaluation indicators of local governments, optimize the structure of government expenditure, and improve the efficiency of the use of government health expenditure.Keywords: fiscal decentralization, government health expenditure, health outcomes, China's new round of fiscal and tax reforms